THE INFLUENCE OF DRYING MODE ON THE DRYING TIME OF ANCHOVY FISH IN A HYBRID INFRARED-CONVECTIVE DRYER: DRYING TIME CORRELATION AND TAGUCHI ANALYSIS - Minh Ha Nguyen; Luan Nguyen Thanh (Applied Engineering Letters, 2023)
This work assesses the drying time correlation of anchovy fish in a hybrid infrared-convective dryer. The correlation of drying time was determined using the regression method. Moreover, the influence of drying mode on drying time was analyzed via the Taguchi approach. The effects of 0.4-0.8 kW infrared power, 0.5-1.5 m/s air velocity, and 50-70oC air temperature were considered. The maximum error of the value predicted using the drying time correlation and the experimental data was 2.7%. Analysis of the influence of input variables on drying time, performed according to the smaller-the-better criterion, showed an infrared power influence of 79.85%, air temperature influence of 19.30%, and air velocity influence of 0.85%. This result is a good orientation when setting up a drying mode in a hybrid dryer. Furthermore, the Taguchi approach fully visualizes the effects of the input variables on the drying time, which is an effective strategy for the present study.